The Influence of Quick Edu Learning Media on Student Achievement in PAI Subject Grade IX at Junior High School: Pengaruh Media Pembelajaran Quick Edu terhadap Prestasi Belajar Siswa Mata Pelajaran PAI Kelas IX di SMP - Affrida Zulfiana; Istikomah Istikomah (Academia Open, 2022)
Quick Edu media is an online based learning media that is presented in the form of an application. This media is used as an example as well as a new innovation as a learning medium that is not monotonous. Quick Edu media is used to trigger students' enthusiasm in learning so that it will affect their learning achievement. Therefore, this study aims to (1) determine the implementation of Quick Edu Learning Media in PAI Class IX subjects at SMP Negeri 3 Candi Sidoarjo. (2) Measuring the extent of the influence of Quick Edu learning media on improving student achievement in PAI Class IX subjects at SMP Negeri 3 Candi Sidoarjo. The method used in this study is a quantitative study with a population of all Class IX students. The data analysis technique in this study used a simple linear regression formula. Based on the research that has been done, there are several research results, namely: (1) the implementation of Quick Edu learning media for PAI Class IX subjects at SMP Negeri 3 Candi got quite good results. (2) there is a significant effect between Quick Edu learning media on student achievement, with the data obtained, namely 0.001 < 0.005. (3) there are 96% of independent variables influenced by the dependent variable. which means that student achievement is influenced by Quick Edu learning media.